Protein N-glycosylation in eukaryotic microalgae and its impact on the production of nuclear expressed biopharmaceuticals - Mathieu-Rivet, Elodie; Kiefer-Meyer, Marie-Christine; Vanier, Gaëtan; Ovide, Clément; Burel, Carole; Lerouge, Patrice; Bardor, Muriel (Frontiers in Plant Science, 2014)
Microalgae are currently used for the production of food compounds. Recently, few microalgae species have been investigated as potential biofactories for the production of biopharmaceuticals. Indeed in this context, microalgae are cheap, classified as Generally Recognized As Safe (GRAS) organisms and can be grown easily. However, problems remain to be solved before any industrial production of microalgae-made biopharmaceuticals. Among them, post-translational modifications of the proteins need to be considered. Especially, N-glycosylation acquired by the secreted recombinant proteins is of major concern since most of the biopharmaceuticals are N-glycosylated and it is well recognized that glycosylation represent one of their critical quality attribute. Therefore, the evaluation of microalgae as alternative cell factory for biopharmaceutical productions thus requires to investigate their N-glycosylation capability in order to determine to what extend it differs from their human counterpart and to determine appropriate strategies for remodelling the microalgae glycosylation into human-compatible oligosaccharides. Here, we review the secreted recombinant proteins which have been successfully produced in microalgae. We also report on recent bioinformatics and biochemical data concerning the structure of glycans N-linked to proteins from various microalgae phyla and comment the consequences on the glycan engineering strategies that may be necessary to render those microalgae-made biopharmaceuticals compatible with human therapy.